Diffusion-Weighted Imaging of the Head and Neck: Influence of Fat-Suppression Technique and Multishot 2D Navigated Interleaved Acquisitions - Bae, Y.J.; Choi, B.S.; Jeong, H.-K.; Sunwoo, L.; Jung, C.; Kim, J.H. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: DWI of the head and neck can reveal valuable information, but the effects of fat suppression and multishot acquisition on image quality have not been thoroughly investigated. We aimed to comprehensively compare the quality of head and neck DWI at 3T using 2 fat-suppression techniques, STIR, and spectral presaturation with inversion recovery, which were used with both single- and multishot EPI.MATERIALS AND METHODS: Sixty-five study participants underwent 3 DWI sequences of single-shot EPI–STIR, single-shot EPI–spectral presaturation with inversion recovery, and multishot EPI–spectral presaturation with inversion recovery of the head and neck. In multiple anatomic regions, 2 independent readers assessed 5-point visual scores for fat-suppression uniformity and image distortion, and 1 reader measured the contrast-to-noise ratio and ADC.RESULTS: The mean visual score for fat-suppression uniformity was higher in single-shot EPI–STIR than in other sequences (all regions except for the orbital region, P < .05). The mean visual score for image distortion was higher in multishot EPI–spectral presaturation with inversion recovery than in single-shot EPI sequences (all regions, P < .001). Contrast-to-noise ratio was mostly lower in single-shot EPI–STIR than in other sequences (P < .001), and ADC was significantly higher in multishot EPI–spectral presaturation with inversion recovery than in single-shot EPI sequences (P ≤ .001).CONCLUSIONS: Overall, multishot EPI–spectral presaturation with inversion recovery provided the best image quality, with relatively homogeneous fat suppression, less image distortion than single-shot EPI sequences, and higher contrast-to-noise ratio than single-shot EPI–STIR. The measured ADC values can be higher in multishot EPI–spectral presaturation with inversion recovery, which necessitates cautious application of the previously reported ADC values to clinical settings.IRISimage reconstruction using image-space samplingmsEPImultishot EPIRESOLVEreadout-segmented EPI using parallel imaging and a 2D navigatorSPIRspectral presaturation with inversion recoveryssEPIsingle-shot EPICNRcontrast-to-noise ratio